With mental health and wellbeing in mind - Allyson McCollam (Scottish Journal of Residential Child Care)
This paper is based on work undertaken on behalf of the Scottish Development Centre for Mental Health and it explores key challenges in addressing the mental health needs of children and young people who are looked after away from home. It considers some models of working that show promise in building bridges between activities to promote good mental health for all such children, as well as highlighting activities that focus on assessment, care and treatment for those who require such intervention.